Calcium imaging in population of dorsal root ganglion neurons unravels novel mechanisms of visceral pain sensitization and referred somatic hypersensitivity. Issue 4 (April 2021) - Gao, Xinyan; Han, Shu; Huang, Qian; He, Shao‐Qiu; Ford, Neil C.; Zheng, Qin; Chen, Zhiyong; Yu, Shaoyong; Dong, Xinzhong; Guan, Yun
Abstract : Abstract: Mechanisms of visceral pain sensitization and referred somatic hypersensitivity remain unclear. We conducted calcium imaging in Pirt -GCaMP6s mice to gauge responses of dorsal root ganglion (DRG) neurons to visceral and somatic stimulation in vivo. Intracolonic instillation of 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) induced colonic inflammation and increased the percentage of L6 DRG neurons that responded to colorectal distension above that of controls at day 7. Colorectal distension did not activate L4 DRG neurons. TNBS-treated mice exhibited more Evans blue extravasation than did control mice and developed mechanical hypersensitivity in low-back skin and hind paws, which are innervated by L6 and L4 DRG neurons, respectively, suggesting that colonic inflammation induced mechanical hypersensitivity in both homosegmental and heterosegmental somatic regions. Importantly, the percentage of L4 DRG neurons activated by hind paw pinch and brush stimulation and calcium responses of L6 DRG neurons to low-back brush stimulation were higher at day 7 after TNBS than those in control mice. Visceral irritation from intracolonic capsaicin instillation also increased Evans blue extravasation in hind paws and low-back skin and acutely increased the percentage of L4 DRG neurons responding to hind paw pinch and the response of L6 DRG neurons to low-back brush stimulation. These findings suggest that TNBS-induced colitis and capsaicin-induced visceral irritation may sensitize L6 DRG neurons to colorectal and somatic inputs and also increase the excitability of L4 DRG neurons that do not receive colorectal inputs. These changes may represent a potential peripheral neuronal mechanism for visceral pain sensitization and referred somatic hypersensitivity. Abstract : Supplemental Digital Content is Available in the Text.TNBS-induced colitis and noxious visceral inputs increase both L6 and L4 dorsal root ganglion neuronal excitability in mice, a peripheral mechanism for visceral pain sensitization and referred somatic hypersensitivity.